Integrating E-Comic Media in Geography Education: Enhancing Student Understanding of the Hydrosphere's Role in Life Systems - Husain, Al Qomar Nur Mahmud; Soelistijo, Djoko; Masitoh, Ferryati (CV Bumi Spasial, 2024)
Enhancing the quality of education can be achieved by incorporating technology and developing engaging media for students. This research focuses on the development of an educational e-comic covering the hydrosphere and its impact on life, using the ADDIE model—specifically, the stages of Analysis, Design, Development, and Implementation (ADDI). Expert validation confirmed the e-comic’s eligibility with an average score of 93%, classifying it as